2022
DOI: 10.1111/cbdd.14041
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 improves Alzheimer's disease by regulating oxidative stress, apoptosis, and neuroinflammation through Wnt/GSK‐3β/β‐catenin signaling pathway

Abstract: Alzheimer's disease (AD) is a chronic neurodegenerative disorder that can cause cognitive impairment. Ginsenoside Rg1 (Rg1) has a significant neuroprotective effect on animals with memory impairment. However, the mechanism of how Rg1 mediates the Wnt signaling pathway and improves cognitive function by regulating oxidative stress, apoptosis, and neuroinflammation is still unclear. In this study, the spatial memory ability of tree shrews was tested by Morris water maze, the expression levels of amyloid protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 92 publications
0
35
0
Order By: Relevance
“…Recent research showed that Rg1 alleviates cadmium-induced neurotoxicity in vitro and in vivo by attenuating oxidative stress and inflammation [ 74 ]. Rg1 improved oxidative stress, apoptosis, and neuroinflammation in AD [ 75 ] ( Figure 6 ). Therefore, Rg1 can inhibit oxidative stress by acting on neuronal cells in vitro.…”
Section: Mechanismsmentioning
confidence: 99%
“…Recent research showed that Rg1 alleviates cadmium-induced neurotoxicity in vitro and in vivo by attenuating oxidative stress and inflammation [ 74 ]. Rg1 improved oxidative stress, apoptosis, and neuroinflammation in AD [ 75 ] ( Figure 6 ). Therefore, Rg1 can inhibit oxidative stress by acting on neuronal cells in vitro.…”
Section: Mechanismsmentioning
confidence: 99%
“…Moreover, in aging rats induced by isoflurane anesthesia, an inhalation anesthetic frequently used in clinics, which can impair cognition [ 171 ], Rg1 was found to improve CI via increasing the levels of PI3K, AKT, and GSK-3β in the hippocampus [ 154 ]. Otherwise, Rg1 improved the tau hyperphosphorylation, reduced the deposition of Aβ 1–42 , and improved the cognitive deficit of the AD tree shrew via regulating the GSK-3β signaling pathway [ 172 ]. mTOR is confirmed to exert a significant effect on synaptic plasticity and β-amyloid clearance via regulating autophagy [ 173 ].…”
Section: Signaling Pathways Involved In the Treatment Of CI By Ginsen...mentioning
confidence: 99%
“…Ginsenoside Re and Rg1 are tetracyclic triterpenoid derivatives extracted from the roots of Panax ginseng C. A. Meyer. Both of them have anti-inflammatory, antioxidant, and hepatoprotective effect ( Li et al, 2016 ; Zhao et al, 2021a ; Mao et al, 2022 ; Yang et al, 2022 ). Our previous study showed that treatment with ginsenoside Rg1 (Rg1) and ginsenoside Re (Re) can reverse growth inhibition ( Bi et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%